3, 3‐Diethylene Di‐Sulfite (DES) as a High‐Voltage Electrolyte Additive for 4.5 V LiNi0.8Co0.1Mn0.1O2/Graphite Batteries with Enhanced Performances. Issue 4 (19th February 2021) - Li, Shuai; Li, Canhuang; Yang, Tianxiang; Wang, Wenlian; Lu, Jing; Fan, Weizhen; Zhao, Xiaoyang; Zuo, Xiaoxi; Tie, Shaolong; Nan, Junmin
Abstract: A functional electrolyte containing 3, 3‐diethylene di‐sulfite (DES) additive is developed to improve the performances of LiNi0.8 Co0.1 Mn0.1 O2 (NCM811)/graphite batteries, especially at high charging cut‐off voltage of 4.50 V. It is indicated that under the conventional conditions of 25 °C and 1 C after 300 cycles in the voltage range of 2.75–4.30 V, the batteries with 0.25 % DES can increase the maximum capacity retention from 66.61 % to 77.25 % initial discharge capacity compared with the batteries without DES. Especially, when the charge cut‐off voltage is increased to 4.50 V, the batteries with 1 % DES exhibit higher capacity retention (82.53 %) after 150 cycles than the batteries without DES (51.19 %). The electrochemical tests and spectroscopic characterization show that this functional DES electrolyte additive well regulates the anode and cathode interfaces with more stabilized films and smaller impedance, which promotes the interfacial extraction and insertion of Li + . In addition, the interfacial film can inhibit the dissolution of the transition metal element Ni from the cathode and protect the structure stability of NCM811 material. The electrolyte containing DES additive reveals promising prospects in the application of NCM811/graphite batteries. Abstract : The 3, 3‐diethylene di‐sulfite (DES)‐functionalized electrolyte regulates the anode and cathode interfaces with more stabilized films and smaller impedance, and it can effectively improve the performances of LiNi0.8 Co0.1 Mn0.1 O2 (NCM811)/graphite batteries, especially at a high charging cut‐off voltage of 4.50 V. This work not only obtains a high‐performance electrolyte but also can provide an effective strategy to develop the functionalized electrolyte matching high‐nickel NCM/graphite batteries.